Kontribusi Kebun Binatang Taman Rimbo Jambi Terhadap Aspek Sosial Ekonomi, Lingkungan Fisik dan Konservasi Satwa Eksitu - Retno Destiani; Hutwan Syarifuddin; Eva Achmad (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
This study aimed to assess the contribution value of Taman Rimbo Jambi Zoo from the aspect of ex-situ animal conservation, socio-economic, and physical environment. Taman Rimbo Zoo is the only conservation institution in Jambi that has a form as an animal park and it has been established since 1980. Taman Rimbo Zoo is a specific conservation in Jambi that is expected to contribute value from the aspect of ex-situ conservation as the main function, socio-economic community, and physical environment. The opportunity of Taman Rimbo Zoo development is primely considering that there are still few places of flora and fauna recreation that are inexpensive, educative and healthy. The data collection techniques in this study are observation, literature study, and interview. Based on the results obtained, the contribution level of animal conservation aspect is very low (19.8). As the main function of the conservation aspect, it is necessary to prioritize the improvements in its management both in terms of animal welfare in breeding success and reducing mortality rates in the collection of animals. In the other side the contribution level of socio-economic aspect is high (28.8) because the existence of Taman Rimbo Zoo gives the opportunity to the local community in employment, business, and becomes a source of Regional Income for Jambi Province. Meanwhile the physical environment aspect, the contribution level is very low (15.0), it occurs since there is no management or utilization for liquid waste from activities in Taman Rimbo Zoo and the tree species in Taman Rimbo Zoo environment are still not optimal in absorbing pollutants. The achievement of Taman Rimbo Zoo contribution assessment from all aspects is 63.6, which means Taman Rimbo Zoo contribution is still considered low and need an improvement in its management.